(UWB)2: Uncoordinated, Wireless, Baseborn Medium Access for UWB Communication Networks - Benedetto, Maria-Gabriella Di; De Nardis, Luca; Junk, Matthias; Giancola, Guerino (Mobile networks and applications, 2005)
A MAC protocol for Ultra Wide Band (UWB) radio networks named (UWB)2 is proposed. The algorithm exploits typical features of impulse radio such as large processing gain, and is conceived in conjunction with a synchronization strategy which foresees the presence of a synchronization sequence in each transmitted packet. (UWB) 2 adopts a pure Aloha approach; Performance analysis of the synchronization tracking mechanism showed in fact that under the preliminary simplistic hypothesis of an AWGN channel, and for a sufficient number of pulses in the synchronization sequence, a fairly high probability of successful synchronization can be achieved, even in the presence of several users and Multi User Interference (MUI). The multiple access scheme is based on the combination of a common control channel provided by a common Time Hopping (TH) code with dedicated data channels associated to transmitter specific TH codes. Results obtained by simulation indicate that (UWB) 2 can be successfully applied when the number of users spans from a few tens to about one hundred, for data rates ranging from a few thousands to a few hundreds of bits per second. Network throughput was above 99.8% in all considered simulation settings. Such achievement confirms that (UWB) 2 is a suitable and straightforward solution for large networks of terminals using impulse radio for transmission at low bit rates. [PUBLICATION ABSTRACT]